Toxic Ethics: Environmental Genomics and the Health of Populations - Robert, Jason Scott (Bioethics, 2004)
Dealing primarily with implications rather than foundations, and focusing downstream at the expense of upstream prevention, mainstream bioethics is at a toxic watershed. Through an extended analysis of the Environmental Genome Project (EGP), we offer new tools from the philosophy of science and from critical epidemiology to help bioethics to move ahead. Our aim in this paper is not to resolve the moral and conceptual problems we reveal, but rather to outline ways to prevent such problems from arising in future research.